Social spending and aggregate welfare in developing and transition economies - Fiseha Gebregziabher; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Notwithstanding the unprecedented attention devoted to reducing poverty and fostering human development via scaling up social sector spending, there is surprisingly little rigorous empirical work on the question of whether social spending is effective in achieving these goals. This paper examines the impact of government spending on the social sectors (health, education, and social protection) on two major indicators of aggregate welfare (the Inequality-adjusted Human Development Index and child mortality), using a panel dataset comprising 55 developing and transition countries from 1990 to 2009. We find that government social spending has a significantly positive causal effect on the Inequality-adjusted Human Development Index, while government expenditure on health has a significant negative impact on child mortality rate. These results are fairly robust to the method of estimation, the use of alternative instruments to control for the endogeneity of social spending, the set of control variables included in the regressions, and the use of alternative samples.
Keywords: C33; H51; H52; H53; I31; 330; Social spending; human development; aggregate welfare; child mortality; developing countries